Human serum transglutaminase and coeliac disease: correlation between serum and mucosal activity in an experimental model of rat small bowel enteropathy. Issue 7 (July 1989) - D'Argenio, G; Sorrentini, I; Ciacci, C; Spagnuolo, S; Ventriglia, R; de Chiara, A; Mazzacca, G
Abstract : Transglutaminase (TG) activity is increased in the mucosa of patients with coeliac disease. Among 18 patients with untreated coeliac disease we have found a significant decrease (p less than 0.001) in serum levels of TG activity (0.72 (0.23) mU/ml). There was no significant differences between 16 treated coeliacs (1.24 (0.28) mU/ml) and 30 normal controls (1.63 (0.42) mU/ml). To evaluate the connection between serum and mucosal TG activity we used the experimental model of methotrexate induced acute hypoplastic enteropathy in the rat. Transglutaminase activity was unchanged in serum and mucosa 24 and 48 hours after MTX administration, but increased in mucosa (2.606 (0.95) v basal 0.207 (0.026) mU/mg protein, p less than 0.001) and significantly decreased in serum at 72 hours (2.08 (0.38) v basal 5.56 (1.50) mU/ml, p less than 0.001) during intestinal cell proliferation. Activity of the enzyme in the mucosa and serum returned to baseline levels within 120 hours. This experimental animal model helps to explain the data of TG activity in human intestinal mucosa and serum reported in this study. Results are mean (SD).